BUCCAL CELL STAINING EFFECT OF LAWSONIA INERMIS AQUEOUS LEAF EXTRACT - Salomi, Sunyarari Simon; Nathan, I. Dibal; Sani, H. Garba; Joseph, V. Zirahei; Zainab, M. Goni; Sunday, J. Manye (FUDMA Journal of Sciences, 2024)
Lawsonia inermis (henna) is a perennial shrub or plant belonging to the Lythraceae family. Hands, nails, fingers, and even hair can be dyed using henna plants, which are a natural colour. The study aims to examine the use of Lawsonia inermis aqueous extract (local stain) as a substitute for methylene blue in the demonstration of buccal swabs in people. Twelve volunteers offered their time to help gather buccal mucosa samples. The volunteers used tap water and normal saline to rinse their mouths. A wooden spatula was used to scrape the cheeks' buccal surface. Each was applied on a glass slide after being diluted with regular saline. 70% alcohol was used to fix the smear, and it was then let to dry. Methylene blue and Lawsonia inermis aqueous extract were used to stain the smears. Squamous epithelial cells' cytoplasm and nucleus were visible on methylene blue-stained slides. There was no nuclear staining in the squamous epithelial cell stained with Lawsonia inermis aqueous extract. Nevertheless, it stained the nucleus when counterstained with hematoxylin. Lawsonia inermis plus hematoxylin-stained buccal smear present a better result compared to the Lawsonia inermis plus eosin-stained slides. Hence, it can be counterstained with hematoxylin to demonstrate buccal cells.
Keywords: Lawsonia intermis; Buccal smear; Methylene blue; Hematoxylin; Eosin